Music, Identity, and Social Justice: A Narrative Review of Contemporary Approaches - Sa'adah , Sufi Ikrima (Indonesian Scientific Publication, 2024)
Music is a fundamental cultural practice that extends beyond entertainment to shape identity, education, and social justice. This narrative review aims to synthesize contemporary scholarship addressing how music functions as a tool for personal and collective identity construction, pedagogical transformation, and sociocultural engagement. A systematic literature search was conducted using Scopus, PubMed, and Google Scholar, employing keywords such as “music education,” “music and identity,” “cultural influence of music,” “critical pedagogy in music,” and “music and social justice.” Inclusion criteria prioritized peer-reviewed studies published in the last two decades that demonstrated methodological transparency and thematic relevance. The results indicate that music significantly influences identity formation, with empirical evidence showing measurable effects on racial and cultural perceptions among youth, while qualitative studies emphasize the role of pedagogies that foster autonomy and social awareness. Comparative studies highlight the universality of music’s identity-shaping role while also underscoring variations across cultural and geographic contexts. Discussion reveals that systemic factors—including inequitable access, exclusionary curricula, and limited representation—pose challenges to realizing music’s full potential. Inclusive pedagogical strategies and policy reforms are identified as promising pathways to address these barriers, though their effectiveness requires further empirical validation. The review concludes that music is both a cultural and educational resource with profound implications for fostering equity and inclusion. Future research should adopt multi-methodological designs, expand to non-Western contexts, and investigate digital influences on music consumption and identity. These directions are essential for advancing music’s role in education and social justice.